Dataset perilaku pencarian informasi, persepsi, dan pengetahuan wanita hamil mengenai pangan fungsional - Marlina, Ekawati; Kusumaningrum, Dwiatri; Rishadi, Rishadi; Yudhanto, Seno; Sari, Diana Permata; Triasih, Hermin (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2024)
This dataset provides comprehensive information on pregnant women’s information-seeking behavior regarding functional food in Bogor City. In addition, this dataset also includes variables that describe the perceptions and knowledge of pregnant women about functional food. The data was collected through a survey among pregnant women who checked their pregnancies at the Community Health Centre in Bogor City. In the survey, sample selection was conducted using a purposive random sampling method, considering the representation of each health center in Bogor City to ensure more representative results. The potential of using this dataset is vast; various stakeholders, including librarians, government, and researchers, can utilize the dataset. Using this dataset, stakeholders can develop a more effective information service environment on functional foods suitable for pregnant women’s needs. In addition, other researchers can use this dataset to compare pregnant women’s information-seeking behavior, perceptions, and knowledge about functional foods in different regions, thus enriching research in this area.